Trends in Child Poverty and Social Transfers in the Czech Republic, Hungary and Poland: Experiences from the Years after Transition - Michael F. Förster; István György Tóth (Luxembourg Income Study (LIS), 2000)
In our paper we present a comparative analysis of the effects of family policy measures on poverty patterns in the Czech Republic, Hungary and Poland. A special attention is devoted to changes in the extent, depth and composition of poverty, in particular that of the youngest generation. Economic well-being of families is a result of a whole complex of social and economic policies and economic developments. The primary source of family incomes is generated on the labor markets in general. The actual constellation of education, labor market, housing and health policies does have an important effect on the economic well-being of families. Importance and effects of policies directly designed for families, therefore, always depend heavily on a number of other factors. Nevertheless, in this paper we focus on family policy changes and their effects, accompanied by a most necessary short mention of other policies and developments. After discussing some methodological issues, we turn to a brief overview of the main trends of the economy in the Czech Republic, Hungary and Poland, followed by a short description of poverty in the observed countries. In these parts of the paper we draw on our earlier work concerning overall poverty, inequality and the incidence of transfers in the Visegrad countries 2. The third section provides policy descriptions. Types of benefits are compared and described across countries and different reform attempts are highlighted. The fourth part of the paper analyses possible effects of family policies on alleviating poverty. Section five concludes.
Keywords: 330; Kinder; Armut; Lebensstandard; Einkommensumverteilung; Tschechische Republik; Polen; Ungarn